Sex work and war in the early modern Low Countries - Pluskota, Marion (TSEG - The Low Countries Journal of Social and Economic History, 2025)
This response to Marjolein ’t Hart’s Oorlog en ongelijkheid reconsiders her argument about the indirect benefits of war for women by focusing specifically on those engaged in sex work. It argues that although urban sex workers initially profited from the booming wartime economy, the subsequent professionalization of the military and the rise of moral and legal reforms ultimately undermined these gains. It shows that the economic opportunities during war were tempered by harsher scrutiny, prosecution, and cultural marginalization that eroded the legitimacy of sex work. Immediate monetary benefits came at the cost of long-term social and legal disadvantages for these women.